2018
DOI: 10.1177/1479972318755722
|View full text |Cite
|
Sign up to set email alerts
|

Assessing referral and practice patterns of patients with chronic cough referred for behavioral cough suppression therapy

Abstract: The purpose of this exploratory research was to describe current referral and practice patterns for behavioral cough suppression therapy (BCST) throughout the United States, and to assess the need for improving the efficiency of BCST referral patterns. In study I, 126 speech-language pathologists, who treat patients with refractory chronic cough (RCC) in the United States, completed a survey about referral patterns, cough duration, and patient frustration level. In study II, 36 adults with RCC referred for BCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Turner and Bothamley found that common diagnoses had often not been excluded in primary care, and estimated that 87% of patients could have been managed in primary care. Slovarp et al reported that, among patients with refractory CC referred to receive behavioral therapy, the mean cough duration before the therapy, which improved 87% of patients, exceeded two years (23). Thus, selected patients may benefit from earlier referral.…”
Section: Discussionmentioning
confidence: 99%
“…Turner and Bothamley found that common diagnoses had often not been excluded in primary care, and estimated that 87% of patients could have been managed in primary care. Slovarp et al reported that, among patients with refractory CC referred to receive behavioral therapy, the mean cough duration before the therapy, which improved 87% of patients, exceeded two years (23). Thus, selected patients may benefit from earlier referral.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a link between breathing pattern changes, cough and laryngeal function. There are a number of studies that demonstrate the effectiveness of behavioural management of chronic cough [11][12][13]28,29]. Since newer therapies for breathing pattern disorder are being evaluated [30] there may be a role for direct therapy targeting dysfunctional breathing in the management of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether patients with chronic cough may have symptoms of VCD or abnormal vocal fold movement during respirationtermed paradoxical vocal fold movement. These are important issues because it is recognised that many patients do not receive timely or appropriate management (13), since VCD and chronic cough are treated differently by numerous disciplines [14]. Although there are overlapping symptoms in chronic cough and VCD, much of the literature reports distinct clinical profiles between the two conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to simplify this questionnaire and address items and domains that are most important to RCC patients. (203,204), proton pump inhibitors (PPIs) (205), and neuromodulators (206)(207)(208)(209). It also experienced robust validation and has been introduced to studies in other diseases, such as acute cough (125), asthma (122), COPD (210,211), CF (212), IPF (23), and bronchiectasis (127).…”
Section: Mcmaster Cough Severity Questionnairementioning
confidence: 99%